Case Report: Applicability of sedation with nitrous oxide in the management of molar incisor hypomineralization in pediatric patients - Molena, Kelly Fernanda; Lima, Ricardo Barbosa; Furtado, Taíssa Cássia de Souza; Queiroz, Alexandra Mussolino de; Carvalho, Fabrício Kitazono de; Arnez, Maya Fernanda Manfrin; Paula-Silva, Francisco Wanderley Garcia (Frontiers in Dental Medicine, 2022)
Patients with molar-incisor hypomineralization (MIH) may manifest dentin hypersensitivity and difficulties in undergoing dental treatment, including fear, anxiety, and behavior problems in the dental office. Then, the objective of this study was to report a clinical case series using inhaled sedation with nitrous oxide and oxygen as a clinical strategy in the management of MIH pediatric patients during dental treatment. Pediatric patients and their legal guardians were properly informed and data were extracted from clinical charts. Six clinical cases were included, whose patients were between 8 and 12 years old. Of these, 4 were female. The indication of moderate sedation took into account the clinical difficulties related to patients with MIH, such as obtaining anesthesia and cooperation, in addition to odontophobia and dental anxiety. All patients were carefully examined to undergo the sedation technique, including medical history and previous experiences with nitrous oxide inhalation sedation, as well as the vital signs were properly evaluated before, during and after the procedures. The nitrous oxide concentration ranged between 30% and 60%. The procedures were restorative, endodontic or surgical (extractions). In general, the use of sedation contributed to the performance of dental procedures. The use of inhaled sedation helped in behavioral management and during the treatment, increasing the effectiveness of local anesthesia. Patients were cooperative for treatment, while no adverse effects or complications related to sedation were observed. Thus, for the patients in this case series, the use of inhalation sedation with nitrous oxide and oxygen contributed to the clinical management of patients with MIH.